School-Based Intervention Design in Educational Action Research: A Practical Exploration of Enhancing Psychological Contracts among Independent College Teachers - Zhang, Wanting; Arce, Hazel Yahweh L. (Journal of Qualitative Research in Education, 2025)
This study addresses the psychological contract dilemma faced by independent college teachers in the context of institutional transformation, employing an educational action research approach to explore breach mechanisms and repair pathways. The researchers conducted a six-month school-based intervention practice with 15 teachers from diverse disciplinary backgrounds and career stages, collecting data through in-depth interviews, participatory workshops, and reflective journals using triangulation strategies. The findings reveal four key insights: (1) Teacher psychological contract breach is rooted in three overlapping dimensions: identity marginalization (80% of participants experienced "second-class teacher" feelings), structural imbalance between effort and reward (emotional labor reward deficiency reached 4.6/5 points), and long-term suppression of unspoken expectations (86.7% of participants never expressed real demands to management); (2) The collective narrative space created by participatory workshops enabled 93.3% of participants to achieve psychological transformation from isolation to resonance through identifying six core common dilemmas; (3) Expectation articulation and immediate management response constitute the micro-mechanisms of trust reconstruction, though the process involves repetition and doubt; (4) Psychological contract transformation produces significant ripple effects, with teaching innovation behavior increasing by 1.8 points, colleague collaboration frequency growing fourfold, and spontaneous learning communities emerging. The study reveals that the essence of psychological contract repair lies in the reconstruction of respect, trust, and meaning in educational relationships, providing empirical contributions to teacher motivation theory and action research methodology, though sustained improvement requires systematic institutional support beyond individual interventions.